COMMUNICATION SKILLS AND SOCIAL INTERACTION OF CHILDREN WITH AUTISTIC SPECTRUM DISORDERS AT SDN 024 COBLONG BANDUNG - Rizka Apta Aprilia Nasution, - (2021)
Children with autistic spectrum disorders as one part of children with special needs experience barriers to interaction and communication skills. This situation is exacerbated by the behavioral disorders that accompany every autistic child, even this obstacle is the most disturbing in autistic children in interacting and communicating with their environment. This study aims to determine the communication skills and social interaction of children with autism spectrum disorders at SDN 024 Coblong Bandung. The approach used in this research is qualitative with descriptive methods. The subjects in this study were children with autistic spectrum disorders with the initials G while the respondents in this study included class teachers who had taught children with autism spectrum disorders in primary schools, students in the same class as children with autism spectrum disorders, and the parents of child's with autism spectrum disorder. The results showed that G is included in the classification of children with active group autistic spectrum disorders because it is a group of autistic children who can approach others, try to say or ask questions but not for pleasure or for the purpose of social interaction reciprocally. From the research results, G's social interaction ability has a little disturbance, such as G is less able to follow simple conversations. The results showed that the subjects were able to communicate and interact socially, both with teachers and friends while in class and at school, as well as with parents at home. Keywords: Communication Skills, Social Interaction, Children With Autistic Spectrum Disorders.